Abacateiro e oliveira como fontes de matéria prima visando a extração de óleo - Oliveira, Marcelo Caetano de (2011)
In recent years, research has shown that oils rich in monounsaturated fatty acids such as oleic acid bring great benefits to human health. For this reason, both the national and the international market have shown significant growth in the consumption these products. In this sense, both the avocado oil and the olive oil have much higher acids content than other oils commonly consumed in Brazil such as soybeans and corn. Besides, extraction equipment for olive oil is similar to that for avocado including dual purpose machines, which favors their use for a longer period contributing to the viability of the investment. This work was carried out with the objective of evaluating both avocado and olive trees in order to find out both the quality and the quantity of the oil extracted. The first study eleven varieties of avocado had their phenological data in the 2008/2009 and 2009/2010 cycles, as well as the fruits physical and chemical properties and the profile of major fatty acids present in crude oil extracted from the varieties rich in lipids were evaluated. The results indicate that Ouro Verde', 'Quintal', 'Wagner' showed up as earlier, 'Fortuna', 'Imperador', 'Hass', 'Margarida', 'Paulistinha', 'Pedroso' and 'Reis' mid-seasoned and 'Fuerte' and 'Campinas' were late. The varieties Fuerte and Hass presented the best results with 21.07 and 26.12% of oil in the pulp with a predominance of oleic acid in the samples. In the second work was performed in ten varieties of olive trees where they were evaluated for plant phenological characteristics in the 2008/2009, 2009/2010 and 2010/2011 cycles, physical and fat of the fruit, the profile of the major fatty acids present in crude oil extracted from the lipid-rich varieties. The results indicate that the flowering period ranged from July to October, the harvest season ranged from January to March, the earliest varieties were Arbequina and the late ones were Galega, Grappolo 575, and Santa Catalina. Grappolo 561 had the longest transverse diameter Grappolo 541 the highest total mass fruits. The Arbequina and Grappolo 561 had highest lipid content, which met the required quality standards established for olive oil. Therefore, we can conclude that there are varieties of avocado and olive trees which are favorable for the extraction of oil in large scale.